Comprehensive Genomic Profiling of EBV-Positive Diffuse Large B-cell Lymphoma and the Expression and Clinicopathological Correlations of Some Related Genes - Zhou, Yangying (Front Oncol, 2019)
Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (EBV+ DLBCL) is a rare type of lymphoma with a high incidence in elderly patients, poor drug response, and unfavorable prognosis. Despite advances in genomic profiling and precision medicine in DLBCL, EBV+ DLBCL remain poorly characterized and understood. We include 236 DLBCL patients for EBV-encoded mRNA (EBER) in situ hybridization detection and analyzed 9 EBV+ and 6 EBV negative cases by next-generation sequencing (NGS). We then performed fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) to analyze chromosome rearrangements and gene expressions in 22 EBV+ and 30 EBV negative cases. The EBER results showed a 9.3% (22/236) positive rate. The NGS results revealed recurrent alterations in MYC and RHOA, components of apoptosis and NF-κB pathways. The most frequently mutated genes in EBV+ DLBCL were MYC (3/9; 33.3%), RHOA (3/9; 33.3%), PIM1 (2/9; 22.2%), MEF2B (2/9; 22.2%), MYD88 (2/9; 22.2%), and CD79B (2/9; 22.2%) compared with KMT2D (4/6; 66.7%), CREBBP (3/6; 50.0%), PIM1 (2/6; 33.3%), TNFAIP3 (2/6; 33.3%), and BCL2 (2/6; 33.3%) in EBV-negative DLBCL. MYC and KMT2D alterations stood out the most differently mutated genes between the two groups. FISH detection displayed a lower rearrangement rate in EBV+ cohort. Furthermore, KMT2D expression was highly expressed and associated with poor survival in both cohorts. MYC was only overexpressed and related to an inferior prognosis in the EBV+ DLBCL cohort. In summary, we depicted a distinct mutation profile for EBV+ and EBV-negative DLBCL and validated the differential expression of KMT2D and MYC with potential prognostic influence, thereby providing new perspectives into the pathogenesis and precision medicine of DLBCL.